2016
DOI: 10.1590/0102-311x00122215
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the production of AIDS-related stigma among pregnant women living with HIV/AIDS in Rio de Janeiro, Brazil

Abstract: A dinâmica da produção de estigma relacionado à AIDS entre gestantes vivendo com HIV/AIDS no Rio de Janeiro, Brasil La dinámica en la generación del estigma, relacionado con el SIDA, entre gestantes viviendo con VIH/SIDA en Río de Janeiro, Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 18 publications
1
6
0
17
Order By: Relevance
“…Research on PLHIV/AIDS has shown similar profiles, predominating subjects with low or average levels of education, unfavorable socioeconomic conditions, and working as service providers and in retail (Sousa, Ferreira, & Sá, 2013). That may be a result of impoverishment and interiorization of the disease, leading to a higher number of HIV cases among people with lower levels of education and income (Monteiro, Villela, Fraga, Soares, & Pinho, 2016). HIV comorbidities are frequent, which were also shown in the sample studied in this research.…”
Section: Discussionsupporting
confidence: 71%
“…Research on PLHIV/AIDS has shown similar profiles, predominating subjects with low or average levels of education, unfavorable socioeconomic conditions, and working as service providers and in retail (Sousa, Ferreira, & Sá, 2013). That may be a result of impoverishment and interiorization of the disease, leading to a higher number of HIV cases among people with lower levels of education and income (Monteiro, Villela, Fraga, Soares, & Pinho, 2016). HIV comorbidities are frequent, which were also shown in the sample studied in this research.…”
Section: Discussionsupporting
confidence: 71%
“…Em minha etnografia efetuada com três mulheres e mães jovens soropositivas, de camadas populares do Rio de Janeiro (NELVO, 2017), o medo e o estigma, como Monteiro et al, (2016) também haviam identificado, foi presente nas trajetórias das interlocutoras.…”
Section: Introductionunclassified
“…Não obstante, segundo Parker (2012), o estigma é um dos principais motivos que afastam os sujeitos dos centros de testagem para obter conhecimento acerca da condição sorológica. Por outro lado, para entender os estigmas sociais advindos da Aids, deve-se atentar para o processo de hierarquização e desigualdades em certos contextos culturais como sugerem Monteiro et al, (2016). As autoras realizaram um estudo com mulheres de baixa renda no Rio de Janeiro e identificaram que:…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In 2013, a study was designed called GENIH: Gender and Infection in the Context of the HIV/AIDS Epidemic in the City of São Paulo, nested in a broader set of research initiatives aimed at filling the knowledge gap in Brazil on the sexual and reproductive health issues of women living with HIV/AIDS (WLHIV) in different contexts: São Paulo, with the current study, Rio de Janeiro 8 , and Porto Alegre 9 . The GENIH study aimed to compare contexts of social vulnerability and sexual and reproductive behavior of WLHIV versus a sample of women not living with HIV, users of the primary healthcare system, hereinafter referred to as women of the primary healthcare system.…”
Section: Introductionmentioning
confidence: 99%